Mass drug administrations with dihydroartemisinin-piperaquine and single low dose primaquine to eliminate Plasmodium falciparum have only a transient impact on Plasmodium vivax: Findings from randomised controlled trials - Phommasone, K; Van Leth, F; Peto, TJ; Landier, J; Nguyen, T-N; Tripura, R; Pongvongsa, T; Lwin, KM; Kajeechiwa, L; Thwin, MM; Parker, DM; Wiladphaingern, J; et al. (Public Library of Science, 2020)
Background: Mass administrations of antimalarial drugs (MDA) have reduced the incidence and prevalence of P. falciparum infections in a trial in the Greater Mekong Subregion. Here we assess the impact of the MDA on P. vivax infections. Methods: Between May 2013 and July 2017, four villages in each Myanmar, Vietnam, Cambodia and Lao PDR were selected based on high prevalence of P. falciparum infections. Eight of the 16 villages were randomly assigned to receive MDA consisting of three-monthly rounds of three-day courses of dihydroartemisinin-piperaquine and, except in Cambodia, a single low-dose of primaquine. Cross-sectional surveys were conducted at quarterly intervals to detect Plasmodium infections using ultrasensitive qPCR. The difference in the cumulative incidence between the groups was assessed through a discrete time survival approach, the difference in prevalence through a difference-in-difference analysis, and the difference in the number of participants with a recurrence of P. vivax infection through a mixed-effect logistic regression. Results: 3,790 (86%) residents in the intervention villages participated in at least one MDA round, of whom 2,520 (57%) participated in three rounds. The prevalence of P. vivax infections fell from 9.31% to 0.89% at month 3 but rebounded by six months to 5.81%. There was no evidence that the intervention reduced the cumulative incidence of P.vivax infections (95% confidence interval [CI] Odds ratio (OR): 0.29 to 1.36). Similarly, there was no evidence of MDA related reduction in the number of participants with at least one recurrent infection (OR: 0.34; 95% CI: 0.08 to 1.42). Conclusion: MDA with schizontocidal drugs had a lasting effect on P. falciparum infections but only a transient effect on the prevalence of P. vivax infections. Radical cure with an 8-aminoquinoline will be needed for the rapid elimination of vivax malaria.